German translation of the PROMIS® pediatric anxiety, anger, depressive symptoms, fatigue, pain interference and peer relationships item banks - J. Devine; A. Kaman; T. L. Seum; F. Zoellner; M. Dabs; V. Ottova-Jordan; L. K. Schlepper; A.-C. Haller; S. Topf; M. Boecker; J. Schuchard; C. B. Forrest; et al. (SpringerOpen, 2023)
Plain English summary A multitude of questionnaires exist, which are not comparable due to different questions or no available translations. PROMIS is an initiative, which was funded by the National Institute of Health in the US, to build better, i.e., more precise and efficient questionnaires, which can be used and compared worldwide. The PROMIS questionnaires include paper-and-pencil short forms and computerized adaptive tests. So far numerous PROMIS surveys have been created using advanced methodologies. They can be used by health care professionals to assess different aspects of health and compare the results internationally. To allow for international comparability of studies using those questionnaires, they need to be translated. This study reports the thorough translation process of the US-American PROMIS® questionnaires measuring anxiety, anger, depressive symptoms, fatigue, pain interference, and peer relationships in children and adolescents into German. The translation included researchers, children, and parents from Germany, Austria, and Switzerland to ensure that the final German version is fully and equally well understood in all of those German-speaking countries. The article describes the translation process, so that the user can understand the translations and use them in an informed way. The translated German questionnaires are ready for use by researchers and clinicians. ( https://www.healthmeasures.net/search-view-measures ).